IMPLEMENTASI KERJA SAMA INDONESIA DAN TIONGKOK DALAM PENGEMBANGAN FASILITAS PRODUKSI KOMPONEN BATERAI LITIUM-ION UNTUK KENDARAAN BERMOTOR LISTRIK NASIONAL - Syauqi Syifauljanan (2023)
Indonesia does not own the technology to process nickel ore into electric battery components, so cooperation and investment in infrastructure development are needed with those who have the technology. One of the efforts to develop the electric battery component industry is for Indonesia to collaborate with China through Vale Indonesia and Huayou to build a High-Pressure Acid Leaching smelter in the Pomalaa Block which produces Mixed Hydroxide Precipitate. The concepts and theories used are the concept of bilateral cooperation and the theory of foreign direct investment using qualitative methods and descriptive analysis. The results of this study show that the cooperation established by Indonesia and China in the development of the electric battery component industry can still be carried out and results in technology transfer, even though it has several obstacles in the implementation of this cooperation. The Indonesian government also still needs to supervise the implementation of the collaboration carried out by Vale Indonesia and Huayou.